Implementation of convolutional perfectly matched layer for three‐dimensional hybrid implicit‐explicit finite‐difference time‐domain method. Issue 7 (4th April 2019) - Zhang, Kanglong; Zheng, Hongxing; Wang, Lu; Wang, Mengjun; Zhao, Quanming; Li, Erping
Abstract: The hybrid implicit‐explicit (HIE) finite‐difference time‐domain (FDTD) method with the convolutional perfectly matched layer (CPML) is extended to a full three‐dimensional scheme in this article. To demonstrate the application of the CPML better, the entire derivation process is presented, in which the fine scale structure is changed from y ‐direction to z ‐direction of the propagation innovatively. The numerical examples are adopted to verify the efficiency and accuracy of the proposed method. Numerical results show that the HIE‐FDTD with CPML truncation has the similar relative reflection error with the FDTD with CPML method, but it is much better than the methods with Mur absorbing boundary. Although Courant‐Friedrich‐Levy number climbs to 8, the maximum relative error of the proposed HIE‐CPML remains more below than −71 dB, and CPU time is nearly 72.1% less than the FDTD‐CPML. As an example, a low‐pass filter is simulated by using the FDTD‐CPML and HIE‐CPML methods. The curves obtained are highly fitted between two methods; the maximum errors are lower than −79 dB. Furthermore, the CPU time saved much more, accounting for only 26.8% of the FDTD‐CPML method while the same example simulated.